Case report: outcome of anlotinib treatment in breast cancer patient with brain metastases - Zhang, Qiongwen; Yan, Xi; Tian, Ting-Lun; Wu, Xin (Frontiers in Pharmacology, 2024)
Brain metastases (BM) represent a common and severe complication of breast cancer (BC), emerging in approximately 10-16% of all BC patients. The prevalent approach for treating BC patients with BM encompasses a multimodal strategy, combining surgery, whole brain radiation therapy, and stereotactic radiosurgery. Yet, a concrete guideline for localized treatment strategies remains elusive, while systemic treatments like small-molecule-targeted therapy and immunotherapy are still in the clinical trial phase. This case study presents a significant clinical response to anlotinib treatment in a patient with estrogen receptor-negative, progesterone receptorpositive, and human epidermal growth factor receptor 2 (HER2)-positive breast cancer, complicated by BM. After the standard first-line treatment including albumin-bound paclitaxel, trastuzumab and pertuzumab, and a second-line treatment involving pyrotinib, capecitabine, and radiotherapy did not produce the desired results, the patient was then administered anlotinib in combination with pyrotinib and letrozole as a third-line treatment, which led to a partial response (PR). The findings suggest that anti-angiogenic therapy, specifically anlotinib, could be regarded as a promising therapeutic option for BC patients with BM.